2018
DOI: 10.1016/j.bbmt.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of Quality of Life in Patients with Multiple Myeloma Undergoing Autologous Stem Cell Transplantation Through an Outpatient and Inpatient Model

Abstract: Outpatient autologous stem cell transplantation (ASCT) has proven to be feasible in terms of physical morbidity and mortality outcomes, but little data exist on the impact of this procedure on quality of life (QoL). The purpose of this prospective, observational, longitudinal cohort study was to compare the effects of inpatient (n = 76) and outpatient (n = 64) modes of care on QoL in patients with multiple myeloma who underwent ASCT. Patients were treated according to their preference for the inpatient or outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of CLL impact quality of life (QoL) [37], and also the sedentary lifestyle of the majority of cancer patients play a negative effect on QoL [5,6,[37][38][39][40][41][42] and on their survival [11]. However, randomized studies have shown the substantial improvement in QoL of cancer patients due to an adequate program of physical activity [23][24][25]34] and impact the cancer survival [7], since it reduces the peak oxygen consumption, improves physical capacity, increases self-esteem, reduces accumulated stress, and promotes relaxation [8,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PcALCL is a lymphoma with a good prognosis and low mortality, which mainly concerns the elderly. Unfortunately, several patients have had multiple relapses throughout their clinical history, particularly in forms with diffuse skin localization in multiple body districts [42]. The history of these patients is therefore characterized by many therapeutic lines.…”
Section: Discussionmentioning
confidence: 99%
“…Programs vary from a patient to another and consequently, several parameters should be evaluated: the functional state of the various organs, the 4 psychic conditions, the physical-motor skills (strength, flexibility, muscle coordination), the cardiovascular function in stressful conditions, the comorbidities, the associated drug therapy, the social conditions, the habits and feeding capacity [40][41]. All this fundamental in order to organize a network that the patient can constantly follow [42][43][44][45]. Programs include aerobic exercise to increase muscle endurance, exercises to strengthen the extensor muscles of the legs and the upper limbs, useful for doing household chores and other activities of the daily life [46][47][48].…”
Section: Introductionmentioning
confidence: 99%